P311 Facilitates the Angiogenesis and Wound Healing Function of MSCs by Increasing VEGF Production - Liu, Zhihui; Yang, Jiacai; Chen, Yunxia; Chen, Cheng; Wang, Jue; Lee, Yew Mun; Zheng, Wenxia; Shang, Ruoyu; Tang, Yuanyang; Zhang, Xiaorong; Hu, Xiaohong; Huang, Yong; et al. (Frontiers in Immunology, 2022)
As a potential clinical therapeutic cell for injured tissue repair, mesenchymal stem cells (MSCs) have attracted increasing attention. Enhancing the pro-healing function of MSCs has gradually become an essential topic in improving the clinical efficacy of MSCs. Recently, studies have shown that neuronal protein 3.1 (P311) plays a crucial role in promoting skin wound healing, suggesting P311 gene modification may improve the pro-healing function of MSCs. In this study, we demonstrated that increasing the in vivo expression of P311 could significantly enhance the ability of MSCs to lessen the number of inflammatory cells, increase the expression of IL10, reduce the levels of TNF-α and IFN-γ, increase collagen deposition, promote angiogenesis, and ultimately accelerate skin wound closure and improve the quality of wound healing. Importantly, we uncovered that P311 enhanced the pro-angiogenesis function of MSCs by increasing the production of vascular endothelial growth factor (VEGF) in vitro and in vivo. Mechanistically, we revealed that the mTOR signalling pathway was closely related to the regulation of P311 on VEGF production in MSCs. Together, our data displayed that P311 gene modification in MSCs augments their capabilities to promote skin wound closure, which might bring the dawn for its clinical application in the future.